Physicochemical characterisation on selected Malaysian rice varieties as affected by different grinding methods and its application in dry laksa noodle / Asmeda Rajab - Rajab, Asmeda (2018)
In the food industry, flour or fine powder is considered as both end products and intermediate products between unit operations. Many food processes specifically involving whole rice grains frequently require size reduction, which is accomplished by dry or wet grinding methods. However, both methods have some drawbacks in term of the flour characteristics and environmental-wise which called for an alternative method. Thus, this study was carried out with the aim to determine the appropriate soaking and grinding times by using dry, semi-wet and wet grinding methods; as well as to evaluate flours’ characteristics and further develop into food product formulation. The Rice (Oryza sativa L.) used in this study consist of two newly released Malaysian hybrids, namely MR 253 and MR 263; and two other hybrids, MR 211 and MR 220. Characterisation focused on the effects of grinding methods and rice varieties on the physicochemical, morphological, functional and thermal properties of rice flours. First stage was the preliminary study on the soaking and grinding processes of whole rice grains, which were done at different time frames of 4, 6, 8 hours and 4, 6, 8, 10 minutes; respectively. The second and third stages involved the preparation of the Malaysian rice flours and their evaluation through physicochemical and functional analyses and morphological observation as well as on the flours’ thermal and pasting profiles and its rheological behaviour. In the final stage; based on the resulted hydration properties, selected samples of rice flours of semi-wet of variety MR 253, wet of variety MR 220 and wet of variety MR 253 were further incorporated in the application phase which involved the formulation and production of Malaysian dry rice noodle (laksa).The study revealed that the 8 hours soaking and 8 minutes grinding was an appropriate combination procedure in order to obtain rice flour with low percentage of damaged starch content and fine average particle size of starch granules for all three methods. Soaking and grinding times were significantly (p<0.05) strongly correlated with percentage of damaged starch content (r=-0.87); while intermediate correlation was found between grinding times and the average particle size (r=-0.59). Overall, the method of grinding employed has significantly greater impact on the physicochemical and functional characteristics of the rice flours than the differences in rice varieties. Correlation analyses emphasised that percentage of damaged granules plays a significant role in governing the rice flours’ physicochemical properties while average particle size of granules possessed crucial role in determining its functional properties. Scanning electron micrograph images revealed characteristic morphological changes in the granules of rice flour samples, without inducing legion changes in the relative crystallinity, though increase in severity of processing resulted in reduced of peak intensity. Gelatinisation and pasting profiles were affected primarily by the grinding methods. All Malaysian rice flour samples exhibit elastic moduli (G’) higher than viscous moduli (G”) in both oscillatory temperature and frequency sweeps. Dry laksa noodles evaluated through the three point bending test showed that experimental noodle from semi-wet ground flour of variety MR 253 showed significant in strength as reflected through the breaking force data; and as well possessed higher tensile strength and extensibility in its cooked (wet) form which indicates the ability of the noodle strands to hold together during cooking and resist breakdown. Overall acceptability scores revealed that all experimental noodles made from Malaysian ground rice flours were more preferable than the commercial noodle.